2020
DOI: 10.1002/pc.25641
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermomechanical coupling in carbon fibers woven‐ply reinforced thermoplastic laminates: Tensile behavior under radiant heat flux

Abstract: The present work focuses on the thermomechanical behavior of carbon fibers woven‐ply polyphenylene sulfide (PPS thermoplastic)‐based composite materials subjected to the combined action of a tensile mechanical loading and one‐side heat flux (40‐60 kW/m2) representative of fire exposure. An experimental bench was specifically designed to provide an insight in the coupling between a medium heat flux thermal aggression and a tensile mechanical loading (either in monotonic or creep mode) within quasi‐isotropic C/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The carbon fibres reinforced PPS composite have already been used in [2][3][4][5][6]. As for previous studies, the composite material was manufactured using a woven-ply prepreg (T300, 3K, 5HS)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon fibres reinforced PPS composite have already been used in [2][3][4][5][6]. As for previous studies, the composite material was manufactured using a woven-ply prepreg (T300, 3K, 5HS)…”
Section: Methodsmentioning
confidence: 99%
“…Polyphenylene sulfide (PPS) is one of the candidates to substitute thermosetting resins in structural parts that would potentially be exposed to fire. Previous studies have focused on characterization of thermal and mechanical behavior of carbon fibres reinforced PPS composite (C/PPS) composites under very high temperature conditions [2][3][4][5][6]. Results have shown that PPS has excellent properties, including high melting temperature, high glass transition temperature and a very good retention of their mechanical properties under fire conditions.…”
Section: Revised Manuscript With No Changes Markedmentioning
confidence: 99%
“…before extending to the case of heterogeneous temperature fields [15][16][17][18][19]. A specificity in [16][17][18] was to combine the thermal aggression to the mechanical loading (in tension or compression) and to make simultaneous measurements of temperatures and mechanical response through time, up to temperatures above the onset of polymer matrix decomposition.…”
Section: Thermomechanical Coupling In C/pps Laminatesmentioning
confidence: 99%
“…Reinforced PEEK with continuous carbon fibre (CF) can not only overcome the shortcomings of ordinary thermoplastic resins such as poor solvent resistance and low elastic modulus, but also show greatly improved performance. Based on previous reports, PEEK 6,7 composites have been applied to Airbus A340-600 and A382 aircraft structures successively. 8 Interfacial properties affect the transmission and distribution of stress in the composite and the generation and propagation of cracks in it, which have an important impact on the strength, toughness, heat resistance grade and moisture and heat aging resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced PEEK with continuous carbon fibre (CF) can not only overcome the shortcomings of ordinary thermoplastic resins such as poor solvent resistance and low elastic modulus, but also show greatly improved performance. Based on previous reports, PEEK 6,7 composites have been applied to Airbus A340‐600 and A382 aircraft structures successively 8 …”
Section: Introductionmentioning
confidence: 99%